From Blue to Green and Everything in Between: Ideational Change and Left Political Economy after New Labour. (February 2013) - Finlayson, Alan
This article argues that ideational and institutionalist approaches to the study of policy continuity and change should be complemented by research into political ideologies, and with exploration of an 'intermediate' public sphere in which there is extensive intra-ideological dispute. Exploring contemporary left-wing debate about political economy in Britain it is shown that ideational change takes place in the context of disputes rooted in ideological tradition, involving the rearrangement of concepts, the emphasising of some and the marginalisation of others. In the present moment that debate is marked by what may be thought of, heuristically, as 'Keynesian', 'Polanyian', 'Schumpeterian' and 'Schumacherian' points of reference. Assessing the likelihood of this debate developing into a coherent 'crisis narrative' it is shown that the development of the relationship between these poles will be decisive but that at present they stumble over the conceptualisation of 'equality' and 'the state'.